Answer:
18. AE = 6
19. BG = 6
20. CF = 5
21. GF = 2
22. CE = 3
23. AC = 3·√5
24. A_F = 10
25. DA = 3·(√5 - 1)
Explanation:
Whereby the point C is the center of the circle, we have;
CB = CG = CE = 3 = The radius of the circle with center at C
CE = 3
CF = √(4² + 3²) = 5 by Pythagoras' theorem
CF = 5
GF = CF - CG = 5 - 3 = 2
GF = 2
BG = CB + CG = 3 + 3 = 6
BG = 6
Whereby, BC is a tangent to the circle with center, C, we have;
A_F = √(8² + 6²) = 10 by Pythagoras' theorem
A_F = 10
AE = A_F - EF = 10 - 4 = 6
AE = 6
AC = √(6² + 3²) = 3·√5 by Pythagoras' theorem
AC = 3·√5
DA = AC - CD = 3·√5 - 3 = 3·(√5 - 1)
DA = 3·(√5 - 1).